Aryl(dimethylaminomethyl)phosphinic Acid Esters: Syntheses, Structures, and Reactions with Halogen Hydrogen Acids, Tin Halides, and Trimethyl Halosilanes. Issue 30 (9th August 2018) - Lutter, Michael; Jurkschat, Klaus
Abstract : This paper reports the synthesis of the aryl(iodomethyl)phosphinic acid ethyl esters, Ar(ICH2 )P(O)OEt (Ar = Ph, Ar = mesityl), which, via dimethyamination, are converted to the corresponding aryl(dimethylaminomethyl)phosphinic acid ethyl esters, Ar(Me2 NCH2 )P(O)OEt (Ar = Ph, Ar = mesityl). Upon reaction with hydrogen chloride, compound Me2 NCH2 (Ph)P(O)OEt forms its hydrochloride salt as a crystalline material. Depending on the reaction conditions, treatment of Me2 NCH2 (Ph)P(O)OEt with SnCl2 gave either [Me2 HNCH2 (Ph)P(O)OEt][SnCl3 ] or the mixed‐valent dinuclear tin salt [Me2 HNCH2 (Ph)P(O)O4 SnCl2 ][SnCl3 ]2, as its dichloromethane solvate. The reaction of Me2 NCH2 (Mes)P(O)OEt with SiMe3 I gives the diorgano bis(trimethylsiloxy)phosphinium iodide [Me2 NCH2 (Mes)P(OSiMe3 )2 ]I, as its toluene solvate. In solution, it is involved in an equilibrium with Me2 NCH2 (Mes)P(O)OSiMe3 and SiMe3 I. From the hydrolysis of [Me2 NCH2 (Mes)P(OSiMe3 )2 ]I, the hydrogen iodide derivative [Me2 HNCH2 (Mes)P(O)OH]I was obtained as three different solvates. [Me2 NCH2 (Mes)P(OSiMe3 )2 ]I reacted with SnF2 to give a product mixture from which the mixed‐valent tin compound [Sn II 2 Me2 NCH2 (Mes)P(O)2 4 Sn IV F2 ]I2, was isolated. The compounds were characterized by NMR and IR spectroscopy, electrospray ionization mass spectrometry, and single‐crystal X‐ray diffraction analysis. Abstract : Aryl(dimethylaminomethyl)phosphinic acid ethyl esters, Ar(Me2 NCH2 )P(O)OEt (Ar = Ph, Ar = mesityl) undergo ester cleavage with trimethyl iodosilane to give a phosphinium iodide derivative that in turn is in equilibrium with a trimethyl silyl ester. With tin(II) halides, ester cleavage accompanied by redox‐type reactions occurs to give mixed‐valent dinuclear tin salts.